HUBUNGAN PENGETAHUAN IBU TENTANG IMUNISASI DPT DENGAN SIKAP IBU TERHADAP PEMBERIAN IMUNISASI DPT DI DESA HULAWA WILAYAH KERJA PUSKESMAS MONGOLATO KABUPATEN GORONTALO TAHUN 2013 - Andi Akifa Sudirman; Nikartin Pakaya (-, 2021)
Immunization program is intended to decrease morbidity and mortality rate caused by certain diseases. The diseases that can be prevented by immunization. are dysentery, tetanus, whooping cough, measles, seizures and tubercoluse. Immunization also prevents the occurrence of certain infectious diseases. Immunization is a very effective medical intervention form in reducing the mortality rate of infants and toddlers. By having immunization, diseases such as Diphtheria, Pertussis, Tetanus, Hepatitis B, can be prevented. The importance of immunization can be seen from the number of children under five who die from diseases that can be prevented by immunization (PD3I). The purpose of this study was to determine the relationship between knowledge on DPT immunization and mother's attitude in giving DPT immunization in Hulawa Village, Mongolato Medical Center work area, Gorontalo Regency in 2012. The study design used was a cross-sectional analytic design. Population and sample were all mothers who had babies that must receive DPT immunization (1, 2, 3) aged 2 to 8 months in Hulawa Village,  Mongolato Medical Center work area, totaling 38 mothers. Sampling technique used was total sampling technique. Analysis carried out in steps : (1) Univariate analysis by using frequency distribution. (2) Bivariate analysis to examine the relationship between variables by using statistical analysis of Chi - Square Test, the value of significance  (p value) <0.05 or (5%). Chi Square Test results showed the value of X2 (6.446) P value = 0.02 which was smaller than α (0.05), That meant there was relationship between  mother’s knowledge on DPT immunization and mother’s attitude in giving DPT immunization in Hulawa Vlage, Mongolato Medical Center work area, Gorontalo Regency in 2012.